Transferrin-gene expression in the rat mammary gland. Independence of maternal iron status. - Grigor, M R (1990)
Transferrin mRNA concentrations were measured in total RNA isolated from liver and mammary tissue of lactating rats at different stages of lactation. The mammary transferrin mRNA concentration varied in a biphasic manner, increasing up to parturition and then decreasing to undetectable levels at days 5 and 10 of lactation before increasing again markedly in late lactation. The values obtained at day 20 of lactation were double those found in livers of lactating rats. The concentrations of total RNA and mRNA for alpha-casein and alpha-lactalbumin did not change between days 5 and 20 of lactation. Transferrin concentrations were measured in milk from rats fed on an iron-free, a control and an iron-supplemented diet. Although there was a 5-fold difference in the transferrin concentration of samples taken between day 5 and day 20 of lactation, the dietary treatments did not result in significant changes. Maternal serum transferrin concentrations were, however, elevated, and pup haemoglobin concentrations were suppressed for the rats receiving the iron-free diet, indicating an alteration of the iron status of these rats.